Differences in Ferritin and Serum Iron Levels in Elderly Coffee Consumers and Non-Coffee Consumers: Perbedaan Kadar Ferritin dan Besi Serum pada Lansia Pengonsumsi Kopi dan Bukan Pengonsumsi Kopi - Soebagijo Poegoeh Edijanto; Gilang Nugraha; Nurul Qomariyah; Nur Laily Azzakia (Medicra (Journal of Medical Laboratory Science/Technology), 2026)
Elderly people experience a decline in physical function that can affect their quality of life, one of which is a decline in digestive function, namely a reduction in stomach acid production of up to 30%. In Indonesia, many elderly people have a habit of drinking coffee. Coffee contains caffeine and tannin polyphenols, which are known to inhibit iron absorption. These physiological changes and consumption habits have the potential to affect iron metabolism, including serum iron and ferritin levels. This study aims to determine the difference in serum iron and ferritin levels in elderly coffee consumers and non-consumers in RW 8, Simomulyo Baru Village, Sukomanunggal District, Surabaya City. Serum iron levels were examined using the colorimetric method, while ferritin levels were examined using the Hipro A1 tool using the Nephelometry Immunoassay method. Data were analyzed using the Mann-Whitney test. The results showed a significant difference in serum iron levels between coffee consumers and non-consumers (p = 0.029). However, no significant difference was found in ferritin levels between the two groups (p = 0.468). This suggests that coffee consumption may influence fluctuating serum iron levels, but does not significantly impact long-term iron stores as reflected in ferritin levels.